Song of Songs in the Zohar - Moreno-Szypowska, Jadwiga Clea (Filozofia Chrześcijańska, 2023)
The Book of Radiance or Zohar is a book created in medieval Spain. And although it is said that its author was the great rabbi of the beginning of the centuries, Shimon bar Yochai, a deeper analysis, especially linguistic (the work is written in artificial Aramaic, in which Arabic, Greek and romance words are woven) showed that it was actually written by the Castilian Kabbalist Moses of Leon, claiming to be the person who only found the manuscript and copied it in several copies. The Zohar, iconoclastic for ones, is for others the third – after the Torah and Talmud – the most important text of the Jewish religion. It is a kind of summary of the centuries-old wisdom of the Sephardim – both representatives of ecstatic-prophetic Kabbalah and theurgical-theoretical – given in the form of a story about the adventures of Simon bar Yochai, who together with his son and adepts travels through Palestine, meditating on the Hebrew Bible, in particular the Pentateuch. Wanderers in their meditations resort to the authority of the most eminent rabbis, and from the exegesis created from them emerges a specific theory of God's Names constituting the basis for future Jewish mysticism, which, based on the Book of Radiance, will be created in the lands of Safed thanks to, among others, Moses Cordovero and Isaac Luria. This article presents this theory in detail, using explanations of its most important experts, such as D. Matt, Ch. Mopsik, M.A. Ouaknin, G. Scholem and G. Vajda, for a better understanding of the intricacies of the Zohar.